The Use of Artificial Intelligence in English Writing: Experiences and Perceptions of Non-English Major Students in Mainland China - Fengmei, Zou; Yuheng, Huang; Xixia, Wang; Ying, Tan (Gipan, 2025)
Recently, artificial intelligence (AI) has been increasingly used in the field of education to support students learning as new tools have been developed for creating better learning opportunities for the children. Studies have also shown mixed consequences of this type of development as some claim that the use of AI tools reduces students’ creativity while others take it as an essential tool for supporting learning of the current and future generation. In China, students studying at university level have been found to have extensively used the AI for writing in English. This paper explores the experiences and perceptions of non-English major students’ use of AI in writing in a university in Mainland China. A total of 120 students studying non-major subject at a university were selected using the convenience sample technique and the data were collected through survey and interviews. The survey was drawn on "Theory of Technology Acceptance and Use" that categorized the user experiences into five dimensions: performance expectations, effort expectations, social impact, facilitation and intention to use. The findings showed that the use of AI had a positive impact on the improvement of English writing skills of non-English major university students. The implication of this impact is that their motivation for writing enhanced indicating that the university program might need to consider students’ use of AI tools for developing language skills including writing.